1987
DOI: 10.1073/pnas.84.24.9099
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of tumorigenesis: a conserved region in the human and Chinese hamster genomes contains genetically identified tumor-suppressor genes.

Abstract: Regional chromosome homologies were found in a comparison of human lip with Chinese hamster 3p.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1989
1989
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…There has been much speculation that a tumor suppressor gene or genes are located in a syntenic region near the Hbb locus on human Chr 11p15 [31][32][33][34], mouse Chr 7 [5,35], rat Chr 1 [21], and hamster Chr 3 [20]. In the study reported here, LOH was detected in seven tumors, and in six the longer Hbb allele was preferentially maintained over the shorter allele.…”
Section: Preferential Chromosomal Lossmentioning
confidence: 57%
See 1 more Smart Citation
“…There has been much speculation that a tumor suppressor gene or genes are located in a syntenic region near the Hbb locus on human Chr 11p15 [31][32][33][34], mouse Chr 7 [5,35], rat Chr 1 [21], and hamster Chr 3 [20]. In the study reported here, LOH was detected in seven tumors, and in six the longer Hbb allele was preferentially maintained over the shorter allele.…”
Section: Preferential Chromosomal Lossmentioning
confidence: 57%
“…Experimental carcinogenesis in many other species results in Hras1 mutations and associated LOH. In Chinese hamster cells, transfection of mutant Hras1 genes results in LOH on Chr 3, which contains the wild-type Hras1 gene [19,20]. Nmethyl-N-nitrosourea-induced rat mammary tumors have gross chromosomal changes on Chr 1, which is syntenic with human Chr 11 and mouse Chr 7.…”
Section: Introductionmentioning
confidence: 99%
“…1983) and hybridized in situ as previously described (H arper and Saunders. 1981;Stenman and Sager. 1987).…”
Section: In Situ Hybridizationmentioning
confidence: 99%
“…The P2 and P3 probes were 3H-labeled by oligonucleotide labeling (Feinberg and Vogelstein. 1983) and hybridized in situ as previously described (Harper andSaunders, 1981: Stenman andSager, 1987). Hybridization was per formed for 16 h at 37 ° C at probe concentrations of 100 ng/ml hybridization solution.…”
Section: ------1-0 -If----------hi-----0-------------------------h -Omentioning
confidence: 99%